The development of a decision support system for concurrently evaluating changes in instream and floodplain habitats caused by flow modifications - Passero, Elaina, author; Morrison, Ryan, advisor; Ross, Matthew, committee member; Julien, Pierre, committee member (Colorado State University. Libraries, 2020)
Assessments of changes to riverine ecosystems due to flow modifications have historically focused on instream habitat. Thus, considerations of floodplain habitat have often been neglected in assessment tools, creating difficulties for understanding the comprehensive impacts of flow changes to both instream and floodplain environments. To support improved habitat management and protection of naturally variable flows, I developed a decision support system that evaluates both fish and vegetation habitat availability in alternative flow scenarios. This system uses the results of high resolution 2D hydrodynamic models to quantify and map suitable habitat for fish and floodplain vegetation at a range of discharges in a river reach. Depth, velocity, and substrate habitat preference information was used to determine available fish habitat at each modeled discharge. Vegetation habitat was quantified from logistic regression equations relating long-term habitat inundation patterns to probability of occurrence of vegetation. I demonstrate the use of this tool on the Verde River in Arizona, USA. Habitat was evaluated for the historic flow record and two alternative flow scenarios: reduced high flows and reduced baseflows. The two scenarios were compared by evaluating changes in monthly and overall habitat availability, the balance of native and non-native fish habitat, and potential for vegetation movement. Reducing high flows created more habitat for fish with non-natives having the largest increases and led to vegetation encroachment. Reducing baseflows did not affect vegetation habitat, but native and non-native fish habitat was greatly reduced.
Keywords: fish; habitat; environmental flows; streams; floodplain